Emission seismic tomography – the tool to study fracturing and fluidodynamics of the Earth crust - Chebotareva I.Ya. (Общество с ограниченной ответственностью «Георесурсы», 2018)
The article presents the results of seismotomographic monitoring of emission sources associated with fractured zone, tectonic faults and fluid filtration in the high permeable rocks. It is shown that the Earth’s natural seismic noise recorded by surface array can be used to study the geodynamic processes caused by the presence of such inhomogeneities. The source of useful information is the extremely weak spatially coherent component of the seismic wave field – the seismic emission generated by background deformation in the energy-saturated volumes of rocks. Additional external technological and natural impact activates latent volumes of geophysical heterogeneity, which reveals new emission targets hidden in the background state. It makes to conduct additional exploration of the field within a radius of several kilometers during hydraulic fracturing. The article also touches on the history of discovery of the seismic emission phenomenon and the mechanisms of generation of a low-frequency branch of emission as a result of amplitude instability of envelopes of high-frequency acoustic oscillations excited as a result of energetic impact on the medium. Low-frequency emission (1-100 Hz) provides the remote study of high-frequency (1-100 kHz) emission oscillations in the energy-saturated volumes located at a great distance from the seismic array
Keywords: emission seismic tomography; seismic emission; structurally inhomogeneous media; oil and gas field